Software quality from behavioural and human perspectives - Yahaya, Jamaiah; Deraman, Aziz; Hamdan, Abdul Razak (Dr. Sang H. Lee, 2008)
Software quality is evolving beyond static assessment to include behavioural attributes and human aspects.These two groups of attributes are vital and necessary to balance between technical and non-technical (human) aspects in software assessment. PQM or Pragmatic Quality Model is a proposed model of quality, which composes of behavioural and human perspectives in assessment. This model provides opportunity to give priority or contribution of quality attributes to reflect the business requirement. Therefore, it is more practical that can suit different users and purposes. As for our research, PQM is used for assessment of software for certification process. This paper explains in detail this model of PQM.